Agriculture Based on Wireless Sensor Network: Literature Survey - zahraa Al Jebory; Abbas H. Miry; Gregor A. Aramice (Wasit Journal of Engineering Sciences)
This manuscript provides an extensive review of the existing literature regarding the confluence of Wireless Sensor Networks (WSN) and Internet of Things (IoT) innovations in the field of Agriculture. The investigation delves into a variety of systems and frameworks crafted to elevate agricultural methodologies through immediate surveillance and oversight of ecological factors. Essential elements encompass the deployment of diverse sensors, including those for soil moisture, temperature, and humidity, which are vital for refining irrigation practices and promoting effective water utilization. The manuscript underscores the significance of microcontrollers such as Arduino and Raspberry Pi in managing and relaying information to central hubs or cloud platforms for distant access and governance via mobile interfaces. Furthermore, the study addresses the applications of communication protocols like LoRa, ZigBee, and Wi-Fi, which enable extensive and efficient data relay. The incorporation of machine learning strategies for distinguishing crops and weeds, along with the utilization of solar energy to power sensor units, is also scrutinized. The manuscript wraps up by highlighting the transformative potential of IoT and WSN technologies in modernizing smart agriculture, providing avenues for energy-efficient and automated farming solutions.